2016
DOI: 10.1002/chem.201602947
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biology of HPAs: A Family of Ceramide Trafficking Inhibitors

Abstract: In 2001, two years before the disclosure of the CERT-associated Cer transfer machinery, N-(3-hydroxy-1-hydroxymethyl-3-phenylpropyl)alkanamides (HPAs) were described as the first, and to date unique, family of intracellular Cer trafficking inhibitors. The dodecanamide derivative, HPA-12, turned out to be a benchmark as a cellular inhibitor of CERT-mediated de novo sphingomyelin biosynthesis. In only 15 years after its first disclosure, this compound has prompted a growing number of biological and chemical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…CERT obviously contributes to cell survival or cell death in more than one manner and a lowering of CERT expression can also provide advantages to tumor cells. This may also match with a recent study, which revealed a novel function of CERT and CERTL in the classical innate immune response, suggesting CERTL’s participation in apoptotic cell clearance [30]. CERT downregulation may be a way for the tumor cells to attenuate complement activation and thus evade the immune system.…”
Section: Ceramide Transfer Protein (Cert)supporting
confidence: 89%
See 1 more Smart Citation
“…CERT obviously contributes to cell survival or cell death in more than one manner and a lowering of CERT expression can also provide advantages to tumor cells. This may also match with a recent study, which revealed a novel function of CERT and CERTL in the classical innate immune response, suggesting CERTL’s participation in apoptotic cell clearance [30]. CERT downregulation may be a way for the tumor cells to attenuate complement activation and thus evade the immune system.…”
Section: Ceramide Transfer Protein (Cert)supporting
confidence: 89%
“…It is structurally related to ceramide and shows potent cellular activity at concentrations between 0.1 to 2.5 µM (Figure 2). Since then, various syntheses and derivatives of HPA-12 have been published [30,32]. Very recently, the first not ceramide-related CERT inhibitor, HPCB-5, was identified by a virtual screening approach [33].…”
Section: Ceramide Transfer Protein (Cert)mentioning
confidence: 99%
“…Most ceramides are then transported to the Golgi to be converted into glycosphingolipids and sphingomyelin. Ceramide transport protein (Cert) mediates ceramide transport for sphingomyelin biosynthesis, which can be inhibited by HPA-12 (Berkes et al, 2016; Duris et al, 2011; Hanada, 2014, 2017; Hanada et al, 2003; Kumagai et al, 2005; Santos et al, 2015). Conversion of ceramide to glucosylceramide is the first step in biosynthesis of raft-associated glycosphingolipids and it is catalyzed by glucosylceramide synthase, a Golgi resident enzyme inhibited by l-phenyl-2-decanoylamino-3-morpholino-1-propanol (PDMP) or deoxynojirimycin-type compounds (Bieberich et al, 1999; Gu et al, 2017; Mellor et al, 2004).…”
Section: Detection Preparation and Visualization Of Rafts And Theirmentioning
confidence: 99%
“…2B). We inhibited the activity of CERT in muscle cells by using the CERT inhibitor HPA12 (18). HPA12 inhibited CERT activity through its interaction with the stAR-related lipid-transfer domain of CERT that usually binds ceramides (30).…”
Section: Influence Of the Modulation Of Cert Activity/ Expression On mentioning
confidence: 99%